When rich pictorial information backfires: The interactive effects of pictures and psychological distance on evaluations of tourism products. (August 2021) - Jia, Yanli; Ouyang, Jun; Guo, Qiang
Abstract: Using data from five studies (i.e., a pilot study and four experiments), we examine the interactive effects of pictures and psychological proximity on consumers' evaluation of tourism products. The extant literature has suggested that providing rich pictorial information or construing a psychologically proximal tourism product can independently increase consumers' generation of mental images and render a positive attitudinal judgment. However, our findings on the effectiveness of these two strategies in combination are mixed . Specifically, we find that if the tourism product is a psychologically distal one, consumers evaluate it more favorably when rich pictorial information is provided than when the information is not available. If the product is a psychologically proximal one, the reverse is true. Our findings, therefore, suggest an important situation that might be intriguing to both tourism product managers and advertisers --when rich pictorial information backfires.